Can Google Analytics Certification Cultivate PR Students’ Competency in Digital Analytics? A Longitudinal Pedagogical Research - Meng, Juan and Jin, Yan and Lee, Yen-I and Kim, Solyee (Journalism & Mass Communication Educator, 2019)
This longitudinal pedagogical research investigates students’ perceptions and learning outcomes by integrating web and social analytics–based learning activities (i.e., Google Analytics courses and certification test) into Public Relations Research course design. Results from the pretest before introducing the analytics learning assignment confirmed that students’ knowledge on web and social analytics is low but their desire to learn is high. Results from the posttest after passing the certification test indicated students are eager to have more experience-based learning activities to apply knowledge related to web and social analytics in public relations research and practice. More pedagogical recommendations are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDc3Njk1ODE4ODE2OTE2